The effect of titanium nitride thickness as a support layer for carbon nanotubes growth - Ramli, Muhammad M.; Osman, N. H.; Darminto, D.; Abdullah, M. M. A. B. (Institute of Metallurgy and Materials Science of Polish Academy of Sciences ; Committee of Materials Engineering and Metallurgy of Polish Academy of Sciences, 2022)
The effect of titanium nitride (TiN) thickness as the support layer for carbon nanotubes (CNTs) growth was investigated by depositing three different thicknesses: 20 nm, 50 nm and 100 nm. This TiN support layer was deposited on SiO2 pads before depositing nickel (Ni) as the catalyst material. The Ni distribution on different TiN thicknesses was studied under hydrogen environment at 600°C. Then, the samples were further annealed at 600°C in acetylene and hydrogen environment for CNTs growth. The results show that, the optimum TiN thickness was obtained for 50 nm attributed by the lowest D to G ratio (0.8).